The Effect of Educational Intelligent Technologies on the Academic Achievement of Elementary Students in Shiraz District One - Hashemi, Seyyed Ahmad; Nabavizadeh, Zahra (IJRDO- Journal of Educational Research, 2017)
The present study was conducted to determine the effect of using Educational IntelligentTechnologies on the academic achievement of primary school students in Shiraz District one.The method of this study was semi-experimental, pre-test and post-test with control group. Thepopulation of this study was elementary school students in Shiraz District one, which 80 studentswere selected through a census method from schools equipped with Educational IntelligentTechnologies facilities. After the pre-test, the content of the course was presented in eightsessions using intelligent technology and also traditionally for the experimental group, andfinally, the academic achievement questionnaire with the same questions from the two groupswas done. Based on the statistical sample, 80 questionnaires have been distributed. All of thequestionnaires are valid and can be cited for data analysis. The research tool in this studyincluded two researcher-made questionnaires of Educational Intelligent Technologies andValerand Students’ Educational Achievement. The validity of the questionnaires was evaluatedbased on the experts' opinion and also on the basis of Bartlett's test. The Educational IntelligentTechnologies Questionnaire had a reliability of 0.765 and academic achievement of 0.742 andtheir reliability based on Cronbach's alpha coefficient for Intelligent Learning Inventory was0.712. And academic achievement was estimated to be 0.894, which indicates the desirablereliability of the research questionnaire. In this study, linear regression analysis and Friedmantest have been used. The results of this study showed that Educational Intelligent Technologieshas a significant effect on the educational achievement of elementary school students in ShirazDistrict one.